Evolution of antimicrobial resistance in E. coli biofilm treated with high doses of ciprofloxacin - Nesse, Live L.; Osland, Ane Mohr; Asal, Basma; Mo, Solveig Sølverød (Frontiers in Microbiology, 2023)
The evolution of antimicrobial resistance (AMR) has mainly been studied in planktonic bacteria exposed to sub-inhibitory AM concentrations. However, in a number of infections that are treated with antimicrobials (AM), the bacteria are located in biofilms where they tolerate high doses of AM.In the present study, we continuously exposed biofilm residing E. coli at body temperature to high ciprofloxacin (CIP) concentrations increasing from 4 to 130 times the minimal inhibitory concentration (MIC), i.e. from 0.06 to 2.0 mg/L. After one week, the biofilms were full of CIP resistant bacteria. The evolutionary trajectory observed was the same as described in the literature for planktonic bacteria, i.e. starting with a single mutation in the target gene gyrA followed by mutations in parC, gyrB and parE, as well as in genes for regulation of multidrug efflux pump systems and outer membrane porins. Strains with higher numbers of these mutations also displayed higher MIC values. Furthermore, the evolution of CIP resistance was more rapid, and resulted in strains with higher MIC values, when the bacteria were biofilm residing than when they were in a planktonic suspension. These results may indicate that extensive clinical AM treatment of biofilm-residing bacteria may not only fail to eradicate the infection but also pose an increased risk of AMR development.